Efficiency evaluation of common forensic genetic markers for parentage identification involving close relatives. (April 2023) - Zhang, X.R.; Meng, H.T.; Shi, J.F.; Wang, N.; Wang, Z.Y.; Zhang, B.; Zhu, B.F.; Guo, Y.X.
Abstract: To explore the efficacy of commonly used forensic identification panels in complex paternity testing of trios that involved close relatives, we wrote a code by R to generate 10, 000 pedigrees at 20 CODIS STR, 21 non-CODIS STR and 30 InDel loci in Chinese five ethnic groups based on their allele frequencies. Parentage identification index——cumulative paternity index (CPI) value was set as output and was further analyzed to evaluate the performance of the aforementioned panels in complex paternity testing when the alleged parent is a random individual, biological parent, grandparent, sibling of biological parent, half-sibling of biological parent, etc. The results showed that the false inclusion of parent sibling posed as parent demonstrated no statistically significant difference from that of grandparent posed as parent. The scenarios where both biological parent and alleged parent were consanguineous to the other parent were also simulated. The results revealed that the complexity of paternity testing would raise when biological parents were consanguineous and the alleged parent was a close relative of theirs. Despite the values of non-conformity number could vary in different genetic relationships, populations and panels, 20 CODIS STRs and 21 non-CODIS STRs performed satisfactorily in most simulated scenarios. However, the joint use of 20 CODIS STRs and 21 non-CODIS STRs is more recommendable when resolving the paternity testing of the incest mating case. Overall, the current study could be regarded as a worthwhile reference in complex paternity testing of trios that involved close relatives. Highlights: Thoroughly compared the efficiency of 3 commonly used commercial kits in complex paternity testing among 5 populations. 11 Scenarios were simulated to analyze the influence of close relatives on paternity testing. The marker set combined CODIS and non-CODIS STRs provides a powerful tool for complex paternity testing.